The The influence of leadership style and work discipline on employee performance with work motivation as an intervening variable in the case study of nurses at Persahabatan Hospital - Zulkifli Zulkifli; Dewi Susita; Corry Yohana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the influence of leadership style and work discipline on employee performance with work motivation as an intervening variable. This study was conducted at Persahabatan Hospital using quantitative methods. Data were collected through questionnaires distributed to 220 employees. The analysis method used is Explanatory research, which is a study conducted to explain the causal relationship between research variables through hypothesis testing. The results of the study indicate that leadership style has a significant effect on employee work motivation and performance. Work discipline was also found to have a significant effect on employee work motivation and performance. In addition, work motivation as an intervening variable has been shown to have a significant effect on employee performance. Explanatory research indicates that work motivation strengthens the influence of leadership style and work discipline on employee performance. Thus, it can be concluded that leadership style and work discipline directly and indirectly through work motivation have a positive effect on employee performance. This finding implies the importance of implementing an effective leadership style and increasing work discipline to improve employee motivation and performance at Persahabatan Hospital.